Timing of procedural stroke and death in asymptomatic patients undergoing carotid endarterectomy: individual patient analysis from four RCTs. Issue 6 (12th March 2020) - Poorthuis, M H F; Bulbulia, R; Morris, D R; Pan, H; Rothwell, P M; Algra, A; Becquemin, J-P; Bonati, L H; Brott, T G; Brown, M M; Calvet, D; Eckstein, H-H; et al.
Abstract: Background: The effectiveness of carotid endarterectomy (CEA) for stroke prevention depends on low procedural risks. The aim of this study was to assess the frequency and timing of procedural complications after CEA, which may clarify underlying mechanisms and help inform safe discharge policies. Methods: Individual-patient data were obtained from four large carotid intervention trials (VACS, ACAS, ACST-1 and GALA; 1983–2007). Patients undergoing CEA for asymptomatic carotid artery stenosis directly after randomization were used for the present analysis. Timing of procedural death and stroke was divided into intraoperative day 0, postoperative day 0, days 1–3 and days 4–30. Results: Some 3694 patients were included in the analysis. A total of 103 patients (2·8 per cent) had serious procedural complications (18 fatal strokes, 68 non-fatal strokes, 11 fatal myocardial infarctions and 6 deaths from other causes) [Correction added on 20 April, after first online publication: the percentage value has been corrected to 2·8]. Of the 86 strokes, 67 (78 per cent) were ipsilateral, 17 (20 per cent) were contralateral and two (2 per cent) were vertebrobasilar. Forty-five strokes (52 per cent) were ischaemic, nine (10 per cent) haemorrhagic, and stroke subtype was not determined in 32 patients (37 per cent). Half of the strokes happened on the day of CEA. Of all serious complications recorded, 44 (42·7 per cent) occurred on day 0 (20 intraoperative, 17 postoperative, 7 with unclear timing), 23 (22·3 per cent) on days 1–3 and 36 (35·0 per cent) on days 4–30. Conclusion: At least half of the procedural strokes in this study were ischaemic and ipsilateral to the treated artery. Half of all procedural complications occurred on the day of surgery, but one-third after day 3 when many patients had been discharged. Graphical Abstract: At least half of the procedural strokes in this study were ischaemic and ipsilateral to the treated artery. Half of all procedural complications occurred on the day of surgery, but one-third after day 3 when many patients had been discharged. Reported in-hospital stroke or death rates might underestimate true risks after carotid endarterectomy. Half the strokes occurred after the day of surgery